On translation between (semi-)peripheral languages: an overview of the external history of Polish literature translated into European Portuguese - Pięta, Hanna (2017)
This article takes as its point of departure the premise that socalled (semi-)peripheral languages, such as Polish and Portuguese, are overlooked in translation research, despite the fact that they provide a useful framework for the investigation of the complex power relations between cultural peripheries and intermediary centres. To address this gap, this descriptive-explanatory article foregrounds these languages by oﬀering an overview of the main patterns in the external (contextual) history of Polish literary texts translated into European Portuguese between 1855 and 2010. First, the article examines the theoretical framework, namely the concepts of external translation history and polysystem. Second, it considers the methodological parameters that guided the research and outlines the historical context in which the analysed translations were embedded. Third, the article discusses the results of the data analysis, structured around six key questions that guided the study. To this end, it describes and explains the salient patterns that emerge from the ﬁndings. Finally, the article presents the conclusions of this study and explores some suggestions for future research.